Increasing Organizational Citizenship Behavior Through Quality of Work Life and Organizational Commitment - Endang Susilawati; Shofia Amin; Musnaini Musnaini (Asosiasi Fakultas Ekonomi dan Bisnis Indonesia, 2021)
This study aims to examine the effect of Quality of Work Life on Organizational Citizenship Behavior through Organizational Commitment as a mediating variable. The population in this study were all permanent employees of PT. Petro China International Jabung Ltd with a sample of 120 respondents. The data collection method uses questionnaire method which is measured using Likert scale and the hypotheses was tested by using the PLS (Partial Least Square) program. The results showed that the quality of work life has positive and significant effect on Organizational Citizenship Behavior, the quality of work life is proven to have positive and significant effect on organizational commitment, organizational commitment has positive and significant effect on Organizational Citizenship Behavior, and organizational commitment partially mediates the relationship between the quality of work life and Organizational Citizenship Behavior. The implication of this research is that the increasing quality of work life will increase organizational commitment so that it can improve Organizational Citizenship Behavior. The company must continuously improve the quality of work life program to increase the employee performance with objective and systematic procedures.